Notifiche
Cancella tutti

iNTEGRALE DEFINITO

  

1

 

121

Risolvere senza la tecninca X SOSTITUZIONE.

Autore
1 Risposta



2

(x - 2)/(x^2 + 3·x + 2)=

=(x - 2)/((x + 1)·(x + 2))

fratti semplici:

(x - 2)/((x + 1)·(x + 2)) = Α/(x - 1) + Β/(x + 2)

(x - 2)/((x + 1)·(x + 2)) =

=(x·(Α + Β) + 2·Α - Β)/((x - 1)·(x + 2))

{Α + Β = 1

{2·Α - Β = -2

Risolvo:  [Α = - 1/3 ∧ Β = 4/3]

∫((x - 2)/(x^2 + 3·x + 2)) dx= 4·LN(x + 2) - 3·LN(x + 1)

Valutato in x =1

4·LN(1 + 2) - 3·LN(1 + 1) = LN(81/8)

Valutato in x =0

4·LN(0 + 2) - 3·LN(0 + 1) = 4·LN(2)

Quindi: LN(81/8) - 4·LN(2) = LN(81/128)=

=4·LN(3) - 7·LN(2)



Risposta
SOS Matematica

4.6
SCARICA